Building dynamic business financing information for enhanced agricultural SME innovations in Uganda - Buwule, Robert Stalone (Qualitative and Quantitative Methods in Libraries, 2021)
Highly innovative Small and Medium Enterprises (SMEs) generally provide additional societal and economic benefits to countries through several ways like; technology uptake, enhancing the value chain processes, social cohesion, amplifying the comparative advantage and ultimately contributing to national economic growth and development. This study purposed to investigate how SMEs in the Ugandan agricultural sector are adopting the innovations from the Research & Innovation (R&I) information with the help from banks and the different agricultural SME financiers. The study was underpinned by the systems theory and it adopted a positivist research paradigm and an exploratory research design. Quantitative methods epistemology was employed. Quantitative data were collected from a sample of 231 SME respondents in the agricultural sector using semi structured questionnaires. The respondents consisted of proprietors of SMEs in the agricultural sector in the central region of Uganda and their representatives. The findings of the study revealed that; SMEs are accessing innovations from the R&I information from university libraries, SMEs experience certain peculiar difficulties when adopting and applying innovations and the SMEs have a limited awareness of flexible agro-business loans from financial institutions. The study further reveals the SME experiences of applying for these agro-based loans, some of the benefits SMEs have got from patronising these loans, the reasons why many SMEs don’t apply for these loans and suggestion on how to improve business financing information for SME innovations.